Its Not about the Destination, Its about the Journey—Plotting 50 Years of Changing Clinical Trends in Plastic Surgery in a Public Sector Teaching Hospital - Rajan, Sheeja; Menedal, Akshata; Pereira, Carlsen; Chandran, Aswathy; Bhaskaran, Deepak; Mohammad, Najeeb; Thomas, Bestin; Sulochana, Aabha Das (Indian Journal of Plastic Surgery, 2021)
Background The year 2019 marked the 50th anniversary of plastic surgery department of our institution. We present an audit to plot the changing clinical trends in our work in the past five decades.Methods A single-center retrospective cohort study based on the department demographics was performed and compared across the decades from 1969 to 2019.Results In 1969, the relative proportion of reconstructive versus cosmetic surgery procedures was 94.32% versus 5.68%; in 2019 this was 76.25% and 23.75%, respectively. An increase of 22 times increase in outpatient registrations, 13.1 times in total surgeries, 642 times in trauma reconstruction, 290 times for hand surgeries, and 323 times for skin tumor surgeries was noted. Male patients (64.9%) increased every decade more than females (35.1%), mostly for trauma surgery and gynecomastia correction. Proportion of pediatric cleft patients have markedly decreased. Spectrum of surgical procedures have widened. Top five reconstructive surgeries in 2019 were limb trauma reconstruction, skin tumor surgeries, hand surgeries, arterio-venous fistula (AV) creation, and oculoplasty. The most common surgery performed was cleft lip surgery in 1969 and hand surgery in 2019. The top five cosmetic surgeries performed in 2019 were scar revisions, nevus excision, liposuction and gynecomastia correction, rhinoplasty, and otoplasty.Conclusions Data collection and archiving and periodic audits help us study changing trends in our field compared with the global trends. Knowing societal demands will help to improve the resident training in teaching hospitals.
Keywords: changing trends; plastic surgery teaching; surgical audit; trauma reconstruction